2004
DOI: 10.1007/s00268-004-7468-3
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Surgery for Hyperparathyroidism: Indications, Limits, and Late Results—New Philosophy or Expensive Selection without Improvement of Surgical Results?

Abstract: We assessed the "late" results after unilateral parathyroidectomy (PTX) performed for selected indications. From October 1998 throughout March 2001 we operated on 454 patients for hyperparathyroidism (HPT). A positive unifocal (99m)tc-MIBI scan was required for the unilateral approach to be used. Intact parathormone (PTH) measurements were done intraoperatively. Postoperative calcium and PTH serum levels of unilaterally operated patients were checked. Follow-up has been 16.2 months (range 6-40 months). Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A much lower incidence was found in a randomized trial in which two of 46 patients randomized to BNE had an unsuspected additional enlarged parathyroid on the contralateral side [6]. In contrast, multigland disease was observed in 16.5% of 395 patients undergoing routine BNE and in 11.1% of patients treated in an institution where SP is the preferred strategy [24]. One possible explanation of such contrasting figures is that some of the small glands considered to be asymmetric hyperplasia were "overinterpretations" of the operative or histological diagnoses.…”
Section: Intraoperative Findings With Une Vs Bnementioning
confidence: 52%
See 1 more Smart Citation
“…A much lower incidence was found in a randomized trial in which two of 46 patients randomized to BNE had an unsuspected additional enlarged parathyroid on the contralateral side [6]. In contrast, multigland disease was observed in 16.5% of 395 patients undergoing routine BNE and in 11.1% of patients treated in an institution where SP is the preferred strategy [24]. One possible explanation of such contrasting figures is that some of the small glands considered to be asymmetric hyperplasia were "overinterpretations" of the operative or histological diagnoses.…”
Section: Intraoperative Findings With Une Vs Bnementioning
confidence: 52%
“…Many authors have provided retrospective case series demonstrating the feasibility and high success rate of UNE or SP [8][9][10][11][12][13][14][15][16] (Table 1).…”
Section: Unilateral Vs Bilateral Neck Explorationmentioning
confidence: 99%
“…Mortier et al [29] reported their US sensitivity as 50% and attributed this result to the fact that cervical echography is not always performed by endocrine sonographers but rather by general radiologists in local or private centers. These two studies show that experience in neck sonography regardless of the specialty makes a major difference.…”
Section: Discussionmentioning
confidence: 94%
“…Our literature search (Fig. 1) identified 3,141 abstracts, of which 82 observational studies and 6 RCTs, published between 1973 and 2014, were included (Table 1) [17–104]. Most of them were conducted in adults who underwent surgery for PHPT using MIP (70 studies, 9643 patients) or BNE (38 studies, 2471 patients).…”
Section: Resultsmentioning
confidence: 99%